HSV-mediated expression of interleukin-4 in dorsal root ganglion neurons reduces neuropathic pain - Glorioso Joseph C; Mata Marina; Hao Shuanglin; Fink David J (SAGE Publishing, 2006)
Abstract Background To examine the role of inflammatory mediators in neuropathic pain, we used a replication-defective genomic herpes simplex virus (HSV)-based vector containing the coding sequence for the anti-inflammatory peptide interleukin (IL)-4 under the transcriptional control of the HSV ICP4 immediate early promoter, vector S4IL4, to express IL-4 in dorsal root ganglion (DRG) neurons in vivo. Results Subcutaneous inoculation of S4IL4 in the foot transduced lumbar DRG to produce IL-4. Transgene-mediated expression of IL-4 did not alter thermal latency or tactile threshold in normal animals, but inoculation of S4IL4 1 week after spinal nerve ligation (SNL) reduced mechanical allodynia and reversed thermal hyperalgesia resulting from SNL. Inoculation of S4IL4 1 week before SNL delayed the development of thermal hyperalgesia and tactile allodynia, but did not prevent the ultimate development of these manifestations of neuropathic pain. S4IL4 inoculation suppressed non-noxious-induced expression of c-Fos immunoreactivity in dorsal horn of spinal cord and reversed the upregulation of spinal IL-1β, PGE2, and phosphorylated-p38 MAP kinase, characteristic of neuropathic pain. Conclusion HSV-mediated expression of IL-4 effectively reduces the behavioral manifestations of neuropathic pain, and reverses some of the biochemical and histologic correlates of neuropathic pain at the spinal level.